2012
DOI: 10.4269/ajtmh.2012.11-0633
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a School-Based Hygiene Promotion and Sanitation Intervention on Pupil Hand Contamination in Western Kenya: A Cluster Randomized Trial

Abstract: Handwashing with soap effectively reduces exposure to diarrhea-causing pathogens. Interventions to improve hygiene and sanitation conditions in schools within low-income countries have gained increased attention; however, their impact on schoolchildren's exposure to fecal pathogens has not been established. Our trial examined whether a school-based water, sanitation, and hygiene intervention reduced Escherichia coli contamination on pupils' hands in western Kenya. A hygiene promotion and water treatment interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
91
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 105 publications
(102 citation statements)
references
References 32 publications
11
91
0
Order By: Relevance
“…There is some evidence from the literature that improvements to WASH infrastructure and conditions may lead to increased exposure to fecal pathogens. Greene and others found that pupils in schools that received latrines had higher risk of having Escherichia coli on their hands, 23 and the authors hypothesized that this may have been due to increased use of latrines that was not accompanied by commensurate increases in handwashing behavior. Although the DCIM program improved WASH outcomes among beneficiary schools compared with comparison schools, beneficiary schools achieved all 15 WASH outcome criteria at only 25% of visits, and the ones that schools were least likely to meet involved providing handwashing stations with soap and ensuring that there were a sufficient number of clean, genderseparated latrines.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence from the literature that improvements to WASH infrastructure and conditions may lead to increased exposure to fecal pathogens. Greene and others found that pupils in schools that received latrines had higher risk of having Escherichia coli on their hands, 23 and the authors hypothesized that this may have been due to increased use of latrines that was not accompanied by commensurate increases in handwashing behavior. Although the DCIM program improved WASH outcomes among beneficiary schools compared with comparison schools, beneficiary schools achieved all 15 WASH outcome criteria at only 25% of visits, and the ones that schools were least likely to meet involved providing handwashing stations with soap and ensuring that there were a sufficient number of clean, genderseparated latrines.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8] Improvements to WASH at schools have sometimes been shown to reduce diarrheal disease, 6,9 acute respiratory infections, 10 soil-transmitted helminth reinfections, 11 and absence among pupils. 3,12 However, these effects are often not consistent between studies and within studies they are dependent on study context and/or the subgroup of pupils under study.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 However, the best way to achieve consistent handwashing may be different depending on the setting. Tippy-tap handwashing stations have often been used to make access to soap and water convenient when running water is not available, but local preferences and conditions likely matter when considering design.…”
Section: Introductionmentioning
confidence: 99%